A Comprehensive Review of PCSK9 Inhibitors. (20th May 2022) - Coppinger, Caroline; Movahed, Mohammad Reza; Azemawah, Veronica; Peyton, Lee; Gregory, James; Hashemzadeh, Mehrnoosh
Cardiovascular disease (CVD) is the leading cause of death in the United States and worldwide. A major risk factor for this condition is increased serum low-density lipoprotein cholesterol (LDL-C) levels for which statins have been successful in reducing serum LDL-C to healthy concentrations. However, patients who are statin intolerant or those who do not achieve their treatment goals while on high-intensity statin therapy, such as those with familial hypercholesterolemia, remain at risk. With the discovery of PCSK9 inhibitors, the ability to provide more aggressive treatment for patients with homozygous and heterozygous familial hypercholesterolemia has increased. Ezetimibe reduces LDL-C by 15%-20% when combined with statin. 2, 3 Protein convertase subtilisin/kexin type 9 (PCSK9) inhibitors have been found to achieve profound reductions in LDL-C (54%-74%) when added to statins. They have shown dramatic effects at lowering major adverse cardiovascular events (MACE) in high-risk patients 4 with LDL-C levels ≥70 mg/dL and can be used in populations that are statin intolerant or not at goal levels with maximally tolerated statin therapy. PCSK9 inhibitors also produce minimal side effects. Myopathy, a common side effect for patients on statins, has been rare in patients on PCSK9 inhibitors. Randomized trials have shown that reduction in LDL-C has translated to clinical benefits even in patients who have not achieved their LDL-C target.